Bioacoustics of four Scinax species and a review of acoustic traits in the Scinax catharinae species group (Amphibia: Anura: Hylidae) - Hepp, Fábio; Lourenço, Ana Carolina Calijorne [UNESP]; Pombal, José P. (My University, 2017)
Herein, we present new data on the acoustic repertories of Scinax heyeri, S. humilis, S. longilineus, and S. trapi-cheiroi, all of which are species belonging to the S. catharinae species group. Based on the acoustic features of the calling signals of the group’s representatives, we recognize two acoustic patterns: long call (four species) and short call (13 species). We found two- and three-note types for species with long and short calls, respectively. This acoustic diversity of notes is recurrent in the literature about the acoustic repertoire of the S. catharinae group and may be directly related to a functional diversity. The species S. humilis has a unique call that does not match any of the acoustic patterns described, and the calls of S. agilis resemble calls of another species group, the Scinax ruber group. Additionally, we review the call nomenclature of the group and standardize it according to homology criteria: acoustic similarity, relative position, and connection by intermediate taxa between the call structures analysed. The interspecific acoustic differences and similarities found here suggest that bioacoustic features may help solve taxonomic issues and aid in the construction of phylogenetic hypotheses within the S. catharinae group.
Keywords: Atlantic Forest; Bioacoustics; Cerrado; Dendropsophini; Taxonomy; Vocalization